An updated description of Galianthe vaginata (Spermacoceae, Rubiaceae), a species endemic to the Serra da Mantiqueira and Serra do Mar, Southeast Brazil - Carmo, João Afonso Martins; Salas, Roberto Manuel; Simões, André Olmos (Phytotaxa, 2016)
An updated description of Galianthe vaginata is here presented. This species is endemic to the Serra da Mantiqueira and Serra do Mar, Southeast Brazil, and occurs in remnants of the Atlantic forest phytogeographic domain, in the campos de altitude, rocky outcrops, and along trails in montane rainforest. Its bracts, short-styled flowers, fruits and seeds are described and illustrated for the first time. The conspicuously winged stems and the pubescent stipules constitute a combination of diagnostic characters useful for distinguishing G. vaginata from G. polygonoides. Its conservation status is reassessed based on recent collections.